PENETAPAN HARGA JUAL PRODUK DENGAN PENDEKATAN FULL COSTING DAN VARIABEL COSTING PADA UMKM GUNUNG JAYA MAKASSAR - Muhammad Reza Ramdani (Jurnal Bisnis dan Kewirausahaan, 2018)
This study aims to explain knowing how the determination of the selling price made by UMKM Gunung Jaya Makassar Based on Full Costing and Variable Costing. This research is doing technique pengmpulan data by way of observation, data source of this research that is data of cost report year 2017, method of analysis in research is quantitative descriptive. From the results of research that UMKM Gunung Jaya Makasar in determining the cost of goods using a full costing approach because it calculates all elements of production costs into the cost of production. Although UMKM Gunung Jaya Makasar has calculated all the elements of cost in the cost of production.UMKM Gunung Jaya Makasar also not include the cost of factory overhead costs in determining the price of production. UMKM Gunung Jaya to determine the selling price between full costing and variable costing. The high selling price is at full costing position.